Molecular Dynamics Study on the Diffusion Behavior of Water Molecules and the Dielectric Constant of Vegetable/Mineral Oil Blends - Manqing Zhao; Bo Zhang; Jianfei Li; Qiankai Zhang; Huaqiang Li (Molecules, 2023)
Insulating oil plays a crucial role in internal insulation of oil-impregnated transformers. It has been demonstrated in a variety of experimental studies that mineral oil (MO) and vegetable oil (VO) can be blended in different ratios to improve insulation properties; however, the mechanisms underlying this phenomenon remain unclear. In this study, a molecular dynamics (MD) simulation approach was used to investigate diffusion of water molecules in VO/MO blends and dielectric constants of a mixture. The results show that the diffusion coefficient of water molecules is negatively correlated with the proportion of VO; thus, addition of VO helps to improve the insulation properties of a mixture. Due to introduction of strong polar functional groups, a decrease in the diffusion behavior of water molecules can be attributed to an increase in the interaction energy and formation of hydrogen bonds between water molecules and the mixed oil system. There is a direct correlation between the dielectric constant of a mixture and VO content; however, it is very sensitive to water content. The presence of strong polar water molecules or functional groups in a mixture leads to an increase in the dielectric constant, which results in a reduction in insulating properties. Accordingly, presence of polar groups plays an important role in determining the insulating properties of a mixture. To increase the insulation performance of a mixture, it is important to consider the diffusion-inhibiting and dielectric effects of the stronger polar groups in vegetable oil compared to those in mineral oil.